A new software-based technique for low-cost fault-tolerant application - Rebaudengo, M.; Reorda, M.S.; Violante, M. (Annual Reliability and Maintainability Symposium, 2003, 2003)
A new software approach providing fault detection and correction capabilities by using software techniques is described. The approach is suitable for developing commercial-off-the-shelf processor-based architectures for safety-critical applications. Data and code duplications are exploited to provide fault detection and correction capabilities. Preliminary results coming from fault injection experiments support the effectiveness of the method.